Successful treatment of acquired pure red cell aplasia with oral corticosteroids in a patient with B-cell CLL - Dharmshaktu, Pramila (BMJ Publishing Group, 2013)
We present the case of a 57-year-old male patient diagnosed with chronic lymphoid leukaemia (CLL) B-cell type along with moderate anaemia. On follow-up investigations the aetiology of anaemia turned out to be pure red cell aplasia (PRCA) on trephine bone biopsy with an elevated serum erythropoietin level. The patient received blood transfusion support. He showed remarkable improvement on oral corticosteroids (prednisolone 60 mg/daily dose) with no further requirement of blood transfusion over next 3 months. However, when the dose of steroid was tapered down to 10 mg/day, the anaemia reappeared. An increase in the dose of steroid brought the haemoglobin level back to normal. Anaemia in CLL can be due to many reasons, of which PRCA is an uncommon association occurring in only around 1% of patients with CLL and usually refractory to the conventional treatment with steroids. This PRCA secondary to CLL is considered to be immune in origin and a response to combination of immunosuppressive therapy such as steroids, cyclosporine, rituximab is anticipated. Our case responded completely to oral steroids alone.